Utilization of Municipal Solid Waste Incineration Fly Ash for Non-Bearing Masonry Units Containing Coconut Fiber. Issue 16 (28th November 2022) - Tabyang, Wisitsak; Suksiripattanapong, Cherdsak; Wonglakorn, Nattiya; Laksanakit, Chuthamat; Chusilp, Nuntachai
ABSTRACT: This research investigated the properties of coconut fiber (CF) reinforced lateritic soil (LS) mixed with municipal solid waste incineration fly ash (MSWI FA) based geopolymer as a green construction material. The MSWI FA was a by-product of the municipal solid waste burning process to generate electricity. The influence factors studied included LS/MSWI FA ratio, CF content, sodium silicate (Na2 SiO3 )/sodium hydroxide (NaOH) ratio, and NaOH concentration. The unconfined compressive strength (UCS), flexural strength (FS), and microstructure analysis were evaluated. The maximum dry unit weight of specimens increased as the LS/MSWI FA ratio and NaOH concentration increased due to the higher specific gravity of LS and the higher concentration of NaOH. The optimum ingredient mixture for the specimen was found at an LS/MSWI FA ratio of 1/1, an Na2 SiO3 /NaOH ratio of 80/20, an NaOH concentration of 5 molar, and a CF content of 0.5%, which meets the 7-day UCS requirement for non-bearing masonry units and offers the highest FS. The specimen containing CF developed a denser matrix compared to the sample without CF because the addition of CF content promotes a geopolymerization reaction. The P-values of independent parameters were less than 0.05, indicating statistical significance at the 95% confidence level.